THE IMPORTANCE OF SOCIAL SUPPORT FOR ADOLESCENT’S ADJUSTMENT CAPABILITIES OF INDONESIAN MIGRANT WORKER FAMILY - Nadya Nida Hasanah; Alfiasari (Journal of Child, Family, and Consumer Studies, 2023)
Adjustment is an ability to make satisfying relationships between individuals and the surrounding environment. The purpose of this study was to analyze the relationship and influence of parenting style and social support on adolescent adjustment to Indonesian Migrant Workers (PMI) families. This research method uses non-probability sampling method with convenience sampling technique at 10 schools in Kesugihan District, Cilacap Regency, Central Java. This study involved 160 junior high school youth whose parents were migrant workers abroad. The index of the average parenting style of the mother is better than the index of the average parenting style of the father and the substitute caregiver. The social support from peers and teachers received by adolescents is in the low category. Adolescent adjustment to migrant worker families is in the moderate category. The results showed that the parenting styles of fathers, mothers, substitute caregivers, peer social support, and teachers had a significant positive relationship with adolescent self-adjustment as well as a significant positive effect on adolescent self-adjustment in PMI families.